The role of cholesterol in cancer - Kuzu, Omer F. (Cancer Res, 2016)
The roles played by cholesterol in cancer development and the potential of therapeutically targeting cholesterol homeostasis is a controversial area in the cancer community. Several epidemiological studies report an association between cancer and serum cholesterol levels or statin use, while others suggest that there is not one. Furthermore, the Cancer Genome Atlas (TCGA) project using next-generation sequencing has profiled the mutational status and expression levels of all the genes in diverse cancers, including those involved in cholesterol metabolism, providing correlative support for a role of the cholesterol pathway in cancer development. Finally, preclinical studies tend to more consistently support a role of cholesterol in cancer with several demonstrating that cholesterol homeostasis genes can modulate development. Due to space limitations, this review provides selected examples of the epidemiological, TCGA and preclinical data, focusing on alterations in cholesterol homeostasis and its consequent effect on patient survival. In melanoma, this focused analysis, demonstrated that enhanced expression of cholesterol synthesis genes was associated with decreased patient survival. Collectively, the studies in melanoma and other cancer types, suggested a potential role of disrupted cholesterol homeostasis in cancer development but that additional studies are needed to link population based epidemiological data, the TCGA database results and preclinical mechanistic evidence to concretely resolve this controversy.